The impact of caregiver burden on quality of life in family caregivers of patients with advanced cancer: a moderated mediation analysis of the role of psychological distress and family resilience - Panpan Cui; Ming Yang; Hengyu Hu; Chunyan Cheng; Xinyi Chen; Jiaoxia Shi; Shifeng Li; Changying Chen; Hongmei Zhang (BMC, 2024)
Abstract Background The caregiver burden frequently experienced by family members tending to advanced cancer patients significantly impacts their psychological well-being and quality of life (QoL). Although family resilience might function as a mitigating factor in this relationship, its specific role remains to be elucidated. This study aims to probe the mediating effect of psychological distress on the relationship between caregiver burden and QoL, as well as the moderating effect of family resilience. Methods A cross-sectional study was conducted between June 2020 and March 2021 in five tertiary hospitals in China. Data were collected on caregiver burden, family resilience, psychological distress (including anxiety and depression), and QoL. Moderated mediation analysis was performed. Results Data analysis included 290 caregivers. It confirmed the mediating role of psychological distress in the caregiver burden-QoL relationship (P < 0.001). Both overall family resilience and the specific dimension of family communication and problem-solving (FCPS) demonstrated significant moderating effects on the "psychological distress/anxiety-QoL" paths (P < 0.05). The utilization of social and economic resources (USER) significantly moderated the association between depression and QoL (P < 0.05). Conclusions The study corroborates psychological distress's mediation between caregiver burden and QoL and family resilience's moderation between psychological distress and QoL. It underscores the need for minimizing psychological distress and bolstering family resilience among caregivers of advanced cancer patients. Accordingly, interventions should be tailored, inclusive of psychological assistance and promotion of family resilience, particularly focusing on FCPS and USER, to augment the caregivers' well-being and QoL.